Expeditious illustration of layer-cake models on and above a tactile surface. (May 2016) - Lopes, Daniel Simões; Mendes, Daniel; Sousa, Maurício; Jorge, Joaquim
Abstract: Too often illustrating and visualizing 3D geological concepts are performed by sketching in 2D mediums, which may limit drawing performance of initial concepts. Here, the potential of expeditious geological modeling brought by hand gestures is explored. A spatial interaction system was developed to enable rapid modeling, editing, and exploration of 3D layer-cake objects. User interactions are acquired with motion capture and touch screen technologies. Virtual immersion is guaranteed by using stereoscopic technology. The novelty consists of performing expeditious modeling of coarse geological features with only a limited set of hand gestures. Results from usability-studies show that the proposed system is more efficient when compared to a windows-icon-menu-pointer modeling application. Graphical abstract: Highlights: New spatial interaction system to rapidly sketch and explore geological models. Stereoscopic visualization approach to direct manipulation in 3-space. Approach uses the continuous interaction space over a multi-touch surface. Comparative study shows advantage over a mouse+keyboard approach. User study identifies a more efficient solution to model layer-caked models.